Activation loop phosphorylation and cGMP saturation of PKG regulate egress of malaria parasites. - Konstantinos Koussis; Silvia Haase; Chrislaine Withers-Martinez; Helen R Flynn; Simone Kunzelmann; Evangelos Christodoulou; Fairouz Ibrahim; Mark Skehel; David A Baker; Michael J Blackman (PLoS Pathogens)
The cGMP-dependent protein kinase (PKG) is the sole cGMP sensor in malaria parasites, acting as an essential signalling hub to govern key developmental processes throughout the parasite life cycle. Despite the importance of PKG in the clinically relevant asexual blood stages, many aspects of malarial PKG regulation, including the importance of phosphorylation, remain poorly understood. Here we use genetic and biochemical approaches to show that reduced cGMP binding to cyclic nucleotide binding domain B does not affect in vitro kinase activity but prevents parasite egress. Similarly, we show that phosphorylation of a key threonine residue (T695) in the activation loop is dispensable for kinase activity in vitro but is essential for in vivo PKG function, with loss of T695 phosphorylation leading to aberrant phosphorylation events across the parasite proteome and changes to the substrate specificity of PKG. Our findings indicate that Plasmodium PKG is uniquely regulated to transduce signals crucial for malaria parasite development.